Analisis Konsep Kerjasama Eksternal Antar Perpustakaan di Perguruan Tinggi - Yusniah Yusniah; Rahma Sariva Asri; Putri Asa Parent; Nuraina Nuraina (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Library collaboration originally involved collaboration between 2 (two) libraries or more regardless of whether the collaboration used computer assistance or telecommunications facilities or not. The research method used in this study is a qualitative method. Qualitative method is a type of research that aims to comprehensively understand the phenomena experienced by the object of research, such as behavior, perceptions, motivations, actions, etc., through a special natural context. through specific natural contexts, and descriptions in scientific language and methods. This research concludes that collaboration between UMA and UNIMED libraries is the right and strategic thing to advance the library between the two. This collaboration aims to improve institutional relations between the two parties in carrying out educational, research and community service activities, library development, and other matters that have been mutually agreed upon. Keywords: Collaboration, External, Higher Education Libraries